Pengembangan Ekowisata Curug Duwur Bumisari Kecamatan Bojongsari Kabupaten Purbalingga - Karma Iswasta Eka; Suwarno Suwarno; Dedy Irawan (Indonesian Community Service and Empowerment Journal (IComSE), 2021)
Duwur Waterfall at Bumisari is a village located in the district Bojongsari Purbalingga. Bumisari Village has a natural tourist destination that is Curug Duwur managed by Badan Usaha Milik Desa (BUMDES). This tourism object is still in the development stage. The development that has been done is still limited to infrastructure, and one of the things that have not been touched is the promotional media. Methods in the activities used to develop further, especially in attracting visitors are interviews, discussions, observations, and pre-design maps. The writing team also prepared the development through the construction of entrance gates, the improvement of facilities, and the creation of 3D location maps. The results of the development carried out in addition to the form of physical facilities in the form of entrance gates, coloring ladder to waterfalls, also made promotional media through the internet by creating a website with a url http://curugduwurbumisari.blogspot.com, the addition of addresses on google maps and the addition of 3D location maps that have obtained HAKI with the Number EC00202126412. The results of the development increased the number of visitors which originally averaged 350 people per month to 750 people in one month of development. These results show that the addition of gates, improvements in facilities and the creation of maps and internet promotional media affect increasing the number of visitors).